A Genetic Variant in the Seed Region of miR‐4513 Shows Pleiotropic Effects on Lipid and Glucose Homeostasis, Blood Pressure, and Coronary Artery Disease. Issue 12 (December 2014) - Ghanbari, Mohsen; de Vries, Paul S.; de Looper, Hans; Peters, Marjolein J.; Schurmann, Claudia; Yaghootkar, Hanieh; Dörr, Marcus; Frayling, Timothy M.; Uitterlinden, Andre G.; Hofman, Albert; van Meurs, Joyce B. J.; Erkeland, Stefan J.; et al.
<x xml:space="preserve">Abstract</x> In this study, we found that rs2168518 in the seed region of miR‐4513 associates with fasting glucose, LDL‐cholesterol and total cholesterol, blood pressure and risk of coronary artery disease. We identified five miR‐4513 target genes, GOSR2, ANK3, PCSK1, BNC2, and MTMR3, as potential mediators of these associations. We showed two mechanisms through which the SNP affects miR‐4513 function: the mutant allele firstly decreases miR‐4513 expression (Fig. 1) and secondly reduces the ability of miR‐4513 to repress the target genes expression (Fig. 2). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>